Development of an Encyclopedia of Sub-Materials the Role of Biodiversity for Life Class X Based on the Results of Inventory of Medicinal Plants - Gunadi, Audina Tiaradita; Panjaitan*, Ruqiah Ganda Putri; Titin, Titin; Yixuan, Dai (Jurnal IPA & Pembelajaran IPA, 2025)
An educator is required to be able to master methods and choose appropriate learning media, to support a quality learning process. This research aims to determine the feasibility of a sub-material encyclopedia on the role of the diversity of living things for life based on an inventory of medicinal plants as a learning medium. The form of this research is research and development which includes the potential and problem stages related to the importance of learning media as supporting the teaching and learning process, the data collection stage through the results of an inventory of medicinal plants, the encyclopedia preparation stage, the encyclopedia validation stage, and the encyclopedia revision stage in accordance with the suggestions given by a validator. This encyclopedia is assessed based on aspects of presentation, content and language which show that this encyclopedia is suitable for use as a learning medium. The validation results of the encyclopedia media by five validators were analyzed using Lawshe's calculations which showed that from three aspects with eleven criteria a content validity ratio value of 1.00 was obtained in the valid category and the average value of all criteria content validity index was obtained of 1.00 with a valid category so that it is declared suitable for use as learning media